Virus‐induced gene silencing in Catharanthus roseus by biolistic inoculation of tobacco rattle virus vectors. (30th August 2015) - Carqueijeiro, I.; Masini, E.; Foureau, E.; Sepúlveda, L. J.; Marais, E.; Lanoue, A.; Besseau, S.; Papon, N.; Clastre, M.; Dugé de Bernonville, T.; Glévarec, G.; Atehortùa, L.; et al.
Abstract Catharanthus roseus constitutes the unique source of several valuable monoterpenoid indole alkaloids, including the antineoplastics vinblastine and vincristine. These alkaloids result from a complex biosynthetic pathway encompassing between 30 and 50 enzymatic steps whose characterisation is still underway. The most recent identifications of genes from this pathway relied on a tobacco rattle virus‐based virus‐induced gene silencing (VIGS) approach, involving an Agrobacterium‐mediated inoculation of plasmids encoding the two genomic components of the virus. As an alternative, we developed a biolistic‐mediated approach of inoculation of virus‐encoding plasmids that can be easily performed by a simple bombardment of young C. roseus plants. After optimisation of the transformation conditions, we showed that this approach efficiently silenced the phytoene desaturase gene, leading to strong and reproducible photobleaching of leaves. This biolistic transformation was also used to silence a previously characterised gene from the alkaloid biosynthetic pathway, encoding iridoid oxidase. Plant bombardment caused down‐regulation of the targeted gene (70%), accompanied by a correlated decreased in MIA biosynthesis (45–90%), similar to results obtained via agro‐transformation. Thus, the biolistic‐based VIGS approach developed for C. roseus appears suitable for gene function elucidation and can readily be used instead of the Agrobacterium‐based approach, e.g. when difficulties arise with agro‐inoculations or when Agrobacterium‐free procedures are required to avoid plant defence responses.